PERLINDUNGAN HUKUM TERHADAP PETANI PENGGARAP TANAH NEGARA MILIK PERUM PERHUTANI - Iwan Permadi (Arena Hukum, 2016)
AbstractThis paper aims to analyze the legal implications of farmers that are not allowed to work on public land controlled by Perum Perhutani which causes conflicts, especially on land abandoned by Perum Perhutani and determine the form of legal protection against farmers who work the state land ruled by Perhutani to prevent horizontal conflicts between society and Perhutani. The author uses the normative method that is supported by empirical data. Farmers are not allowed to work on land controlled by perhutani because it is considered by Perhutani to be State Land, wherea from the law perspective if the land controlled by Perhutani is abandoned the it becomes free state land that is not entitled. Forms of legal protection against Farmers who work the land ruled by Perhutani state is through preventive and repressive legal protection, namely through the issuance of land titles to the land controlled by the Perhutani but abandoned by Perhutani.Â AbstrakTulisan ini bertujuan untuk menganalisis implikasi hukum petani tidak diperbolehkan menggarap tanah negara yang dikuasai oleh Perum Perhutani Â yang mengakibatkan konflik khususnya pada tanah yang ditelantarkan oleh Perum Perhutani dan mengetahui bentuk perlindungan hukum terhadap Petani yang menggarap tanah negara yang dikuasai oleh Perhutani agar tidak terjadi konflik horizontal antara masyarakat dan Perhutani. Penulis menggunakan metode yuridis normatif yang didukung dengan data empirik. Petani tidak diperbolehkan menggarap tanah yang dikuasai perhutani karena dianggap oleh Perhutani itu adalah Tanah Negara, padahal secara hukum apabila tanah yang dikuasai oleh Perhutani tersebut ditelantarkan maka akan menjadi tanah Negara bebas yang tidak mempunyai alas hak. Bentuk perlindungan hukum terhadap Petani yang menggarap tanah negara yang dikuasai oleh Perhutani adalah melalui perlindungan hukum preventif dan represif, yaitu melalui pemberian hak atas tanah terhadap tanah yang dikuasai oleh Perhutani tersebut tetapi ditelantarkan oleh Perhutani.Â